Böll and the Burgundians: Myth and the (Re)Construction of the German Nation - David N. Coury (Studies in 20th & 21st Century Literature, 2001)
Since its "rediscovery" by the Romantics, the Nibelungenlied has evolved not only into the German national epic, but has come to be synonymous with Germany and "Germanness." After the misappropriation of the saga by the Nazis, the myth, as well as the themes associated with it had become tainted, like all things heralded for their "Germanic" nature, in the immediate post-war era. One of the first writers in the post-war era to again explore the function of myth and recontextualize the saga was Heinrich Böll. Böll set about to reexamine the mythic elements of the story and did so by shifting the frame of reference away from the National Socialist racial manifestations to one with an ethical as well as a historical and spatial determinacy. Realizing that it was the mythic elements of the Lay which helped define Germany's literary identity as well as its own national identity, Böll's references and allusions to the saga in his novels reveal not only a deep attachment to the epic but also Böll's own identification with the German landscape and to a specific moral cultural tradition. In the absence of a body of literature in the post-war period which could thematically help constitute a new German literature, Böll's reincorporation and recontextualization of the Nibelungen mythology helped not only to restore the use of Germanic myth to German literature, but also served as a tool for socio-political critique as well as a means of examining Germany's past and present so as to help explain the consciousness of the individuals and the society populating his literary prose.
Keywords: rediscovery; Romantics; Nibelungenlied; German national epic; Germanness; Germany; Nazis; myth; tainted; themes; Germanic; Germanic nature; post-war era; Heinrich Böll; National Socialist; race; spatial determinacy; ethical; historical; Lay; German Literary identity; identity; national identity; moral; national landscape; moral cultural tradition; cultural tradition; German literature; socio-political critique; past and present; past; present